Anti-Proliferative Effects of Compound A and Its Effect in Combination with Cisplatin in Cholangiocarcinoma Cells - Junking, Mutita (Asian Pac J Cancer Prev, 2020)
BACKGROUND: Cholangiocarcinoma (CCA) is a fatal cancer with high resistance to anticancer drugs. The development of new drugs or compounds to be used alone or in combination with currently available chemotherapeutic agents to improve the treatment of CCA is needed. Compound A (CpdA), which is a small plant-derived glucocorticoid receptor modulator, strongly inhibited the growth and survival of several cancers. However, the effect of CpdA on cholangiocarcinoma has not been elucidated. The aim of this study was to investigate the effect of CpdA on CCA. METHODS: Cytotoxicity of CpdA was tested in primary cells including peripheral blood mononuclear cells (PBMCs), fibroblasts, and human umbilical vein endothelial cells (HUVECs), as well as on CCA cell lines (KKU-100, KKU-055, and KKU-213) was examined. Cell cycle distribution and IL-6 expression was assessed by flow cytometry and real-time polymerase chain reaction, respectively. The effect of combination CpdA and cisplatin was evaluated by cell viability assay. RESULTS: CpdA significantly inhibited cell cycle at G1 phase in CCA cell lines, and reduced IL-6 mRNA expression. However, combination CpdA and cisplatin did not enhance the inhibitory effect. TGFβR-II expression was increased in CCA cells after the combination treatment. CONCLUSIONS: These results indicate the potential of CpdA for CCA treatment. However, combination treatment with CpdA and cisplatin increased CCA cell survival. The molecular mechanism is likely attributable to promotes cell survival via the TGFβR-II signaling pathway. The combination of CpdA with other anticancer drugs for CCA treatment should be further examined.